Prediction of the Carcinogenic Potential of Human Pharmaceuticals Using Repeated Dose Toxicity Data and Their Pharmacological Properties - van der Laan, Jan Willem; Buitenhuis, Wenny H. W.; Wagenaar, Laura; Soffers, Ans E. M. F.; van Someren, Eugene P.; Krul, Cyrille A. M.; Woutersen, Ruud A. (Frontiers in Medicine, 2016)
In an exercise designed to reduce animal use, we analysed the results of rat sub-chronic toxicity studies from 289 pharmaceutical compounds with the aim to predict the tumour outcome of carcinogenicity studies in this species. The results were obtained from the assessment reports available at the Medicines Evaluation Board of the Netherlands for 289 pharmaceutical compounds that had been shown to be non-genotoxic. One hundred and forty-three of the 239 compounds not inducing putative preneoplastic lesions in the sub-chronic study did not induce tumours in the carcinogenicity study (True Negatives - TN), whereas 96 compounds were categorised as False Negatives (FN), because tumours were observed in the carcinogenicity study. For the remaining 50 compounds, 31 showed preneoplastic lesions in the subchronic study and tumours in the carcinogenicity study (True positives - TP), and 19 only showed preneoplastic lesions in subchronic studies but no tumours in the carcinogenicity study (False positives - FP). In addition, we then re-assessed the prediction of the tumour outcome by integrating the pharmacological properties of these compounds. These pharmacological properties were evaluated with respect to the presence or absence of a direct or indirect proliferative action. We found support for the absence of cellular proliferation for 204 compounds (TN). For 67 compounds the presence of cellular hyperplasia as evidence for proliferative action could be found (TP). Therefore, this approach resulted in an ability to predict non-carcinogens at a success rate of 92 % and the ability to detect carcinogens at 98 %. The combined evaluation of pharmacological and histopathological endpoints eventually led to only 18 unknown outcomes (17 categorised as FN. 1 as FP), thereby enhancing both the negative and positive predictivity of an evaluation based upon histopathological evaluation only. The data show the added value of a consideration of the pharmacological properties of compounds in relation to potential class-effects, both in the negative and positive direction. A high negative and a high positive predictivity will both result in waiving the need for conducting 2-year rat carcinogenicity studies, if this is accepted by Regulatory Authorities, which will save , large numbers of animals, reduce drug development